Exosomal lncRNA SCIRT/miR-665 Transferring Promotes Lung Cancer Cell Metastasis through the Inhibition of HEYL. (26th July 2021) - Wang, Zhengyang; Lin, Minmin; He, Lulu; Qi, Hongyan; Shen, Jing; Ying, Kejing
Abstract : Lung cancer remains the leading cause of cancer-related death worldwide. Recently, extracellular vesicles such as exosomes have attracted considerable interest both as a source for theranostic biomarkers and an essential participant in lung cancer progression. However, how specific exosomal cargos, such as noncoding RNAs, are selectively packaged into exosomes and promote lung cancer progression remains unclear. In this study, we identified miR-665 as the most elevated exosomal miRNA from both non-small-cell lung cancer (NSCLC) and small-cell lung cancer (SCLC) patients. We further demonstrated that lncRNA SCIRT was also increased in cancer cell exosomes and may facilitate the exosomal loading of miR-665 with the help of hnRNPA1. As a consequence, exosomal miR-665 promoted lung cancer cell invasion and migration by targeting Notch downstream transcription factor HEYL. In addition, we found that miR-665 and SCIRT were significantly upregulated in tumor tissue and plasma of patients with lung cancer, and both of them showed increased expression in metastatic disease samples. Our findings suggest that the exosomal transferring of miR-665 and SCIRT is a functional and mechanism-driven pathway that contributes to cancer progression and, thus, may provide novel diagnostic and therapeutic targets for lung cancer.